BCG-osis after BCG vaccination in immunocompromised children: Case series and review - Soheila Shahmohammadi; Mohammad Jafar Saffar; Mohammad Sadegh Rezai (Journal of Pediatrics Review, 2014)
Bacillus Calmette Guerin (BCG) developed by Albert Calmette and Camille Guerin in France between 1908 and 1921 contained a live attenuated strain of Mycobacterium bovis and was administered worldwide to prevent tuberculosis. BCG vaccination is also administered at birth to all the newborns in Iran. Disseminated BCG infection after BCG vaccination is rare. Here in, we report 2 new cases of disseminated BCGinfection and review 15 additional cases identified from our previous retrospective study during a 5-year period from 2005-2010. All of these reported patients were vaccinated. Impaired immunity was detected in 10 cases (59%) including severe combined immunodeficiency, chronic granulomatous disease, Mendelian susceptibility to mycobacterial disease, combined variable immunodeficiency, and HIV infection. Response to therapy was poor among those patients with immune deficiencies, but the overall mortality rate was 32.3%. Disseminated BCG infection is a rare but devastating complication of vaccination. Immune-compromised children are at high risk of developing BCG related complications including regional BCG-itis or disseminated disease; BCG-osis.